2016
DOI: 10.2320/matertrans.mi201505
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of Young's Modulus in a Ti-Mo-Al-Zr Alloy with Goss Texture

Abstract: Anisotropy of the Young s modulus and microstructure of a recrystallized β Ti-Mo-Al-Zr alloy with a Goss texture were investigated. Specimens were solution-treated at 1173 K for 3.6 ks after cold rolling with a reduction rate of 99%. The {011}<100> Goss recrystallization texture developed as a major texture component. The Young s modulus was evaluated by tensile tests using a strain gage method. Anisotropy of the Young s modulus depending on the loading direction was observed: The lowest and highest values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The formation of Goss texture of {110} β <001> β has been reported only in a few β-type Ti alloys such as Ti-Mo-Al-Zr, Ti-Zr-Nb-Sn-Mo, and Ti-Nb-Sn. [40][41][42] Although the cause of the change in recrystallization texture due to the change in Sn or Nb content is not clear at present, it is worth noting that the development of the {110} β <001> β texture is very beneficial to achieve low Young's modulus because Young's modulus is minimized along the <001> β direction in β-type Ti alloys.…”
Section: Recrystallization Texturementioning
confidence: 99%
See 1 more Smart Citation
“…The formation of Goss texture of {110} β <001> β has been reported only in a few β-type Ti alloys such as Ti-Mo-Al-Zr, Ti-Zr-Nb-Sn-Mo, and Ti-Nb-Sn. [40][41][42] Although the cause of the change in recrystallization texture due to the change in Sn or Nb content is not clear at present, it is worth noting that the development of the {110} β <001> β texture is very beneficial to achieve low Young's modulus because Young's modulus is minimized along the <001> β direction in β-type Ti alloys.…”
Section: Recrystallization Texturementioning
confidence: 99%
“…[ 34,38,39 ] Recently, it has been reported that very low Young's moduli in the range of 31.5–44 GPa can be achieved in Ti–Mo–Al–Zr, Ti–Zr–Nb–Sn–Mo, and Ti–Nb–Sn alloys by the formation of Goss texture of {110} β <001> β . [ 40–42 ] In particular, a bone‐like elastic modulus of 31.5 GPa was achieved in a Ti–15Nb–5.5Sn (at%) alloy due to the formation of a strong {110} β <001> β texture and the suppression of the α″ martensite phase and ω phase. [ 42 ]…”
Section: Introductionmentioning
confidence: 99%
“…Goss-oriented ({110}<001>) and <001>-fibers are dominantly formed as a recrystallization texture in sheet and cold-groove-rolled (hereafter, simply groove-rolled) wire materials, respectively. In β-Ti, the Young's modulus is lowest along <001> [10,12] and the development of this orientation is effective to reduce the Young's modulus in both sheet and wire materials [11,13]. Particularly for wire materials, it was observed that: (1) stress-induced martensitic transformation (SIMT) from β (bcc) to α″ (corthorhombic) occurs during groove-rolling and (2) the <001>-fiber developed by severe deformation after heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Young's modulus along the RD decreased in sheets with Goss orientation and in coldgroove-rolled wires with ©001ª ¢ -fiber. 24,28) With this background, we state that the formation of Goss orientation is advantageous for biomedical SMAs and implant materials. In our previous study, we investigated the effect of thermomechanical treatment on texture formation in Ti5.5Mo8Al6Zr (mol%) alloy sheets.…”
Section: Introductionmentioning
confidence: 99%